Estimating Southern Ocean Storm Positions With Seismic Observations. Issue 4 (13th April 2020) - Hell, Momme C.; Gille, Sarah T.; Cornuelle, Bruce D.; Miller, Arthur J.; Bromirski, Peter D.; Crawford, Alex D.
Abstract: Surface winds from Southern Ocean cyclones generate large waves that travel over long distances (>1, 000 km). Wave generation regions are often colocated with enhanced air‐sea fluxes and upper ocean mixing. Ocean wave spectra contain information about storm wind speed, fetch size, and intensity at their generation site. Two years of seismic observations on the Ross Ice shelf, combined with modern optimization (machine learning) techniques, are used to trace the origins of wave events in the Southern Ocean with an accuracy of ±110 km and ±2 hr from a hypothetical point source. The observed spectral energy attenuated within sea ice and in the ice shelf but retains characteristics that can be compared to parametric wave models. Comparison with the Modern‐Era Retrospective Analysis for Research and Applications, Version 2, and ERA5 reanalyses suggests that less than 45% of ocean swell events can be associated with individual Southern Ocean storms, while the majority of the observed wave events cannot be matched with Southern Ocean high wind events. Reanalysis cyclones and winds are often displaced by about 350 km or 10 hr in Modern‐Era Retrospective Analysis for Research and Applications, Version 2, and ERA5 compared to the most likely positions inferred from the seismic spectra. This high fraction of displaced storms in reanalysis products over the South Pacific can be explained by the limited availability of remote sensing observations, primarily caused by the presence of sea ice. Deviation of wave rays from their great circle path by wave‐current interaction plays a minor role. Plain Language Summary: Surface winds under storms over the Southern Ocean make large ocean waves that travel over long distances (>1, 000 km). Regions of wave generation coincide with regions where ocean uptake of heat and CO2 is large, so knowledge about wave generation regions helps us to understand the role of the Southern Ocean in the climate system. A 2‐year field campaign made new observations of ocean wave arrivals at the Ross Ice Shelf. These observations are used to trace the origins of the wave events in the Southern Ocean. Even though the waves observed in the sea ice are much smaller than in the open ocean, the observations are good enough to identify ocean waves. The wave arrivals can be used to infer a most likely time and location of the storm that generated the waves. Comparison with two reanalysis products (Modern‐Era Retrospective Analysis for Research and Applications, Version 2, and ERA5) suggests that more than half of the observed ocean wave events cannot be matched to individual Southern Ocean storms. This high percentage of displaced storms in the reanalysis products can be explained by the limited availability of satellite observations caused by the presence of sea ice. Key Points: Ocean swell events are detected in the Ross Ice shelf year‐round, but 45% or less of the swell can be linked with individual storms About 55% or more of the observed swell can only be associated with reanalysis winds whose positions are displaced Reanalysis winds are often displaced when sparse or no observations of surface winds are available, as for example, over or close to sea ice